Physical and Chemical Properties of Rice Husk Ash Concrete Under Seawater - Putra Jaya, Ramadhansyah; Hainin, Mohd Rosli; Wan Ibrahim, Mohd Haziman; Mohamed Nazri, Fadzli; Arshad, Mohd Fadzil; Muthusamy, Khairunisa (International Journal of Integrated Engineering, 2018)
The physical and chemical properties of rice rusk ash concrete under seawater attack are evaluated based on thermogravimetric analysis, X-ray diffraction, and scanning electron microscopy. A rice husk ash dosage of 10% by weight of binder was used throughout the experiments. The results clearly showed that RHA can be satisfactorily used as a cement replacement material in order to increases the durability of concrete under seawater attack. The used of RHA as cement replacement in concrete reduced the quantities of ettringite and gypsum formation. The results indicated that blended cement prepared with RHA reduced the potential for the formation of ettringite and gypsum due to the reduction in the quantity of calcium hydroxide and C3A, and thus improved the resistance of concrete to seawater attack. Furthermore, more formation of ettringite and gypsum was observed from Portland cement concrete compared to the RHA blended cement. Finally, it can be concluded that calcium hydroxide (Ca(OH)2) can be reduce when ground RHA is used as partially replacement cement.